Conceptual framework to incorporate drainage solutions in the urban open space system - Miguez, Marcelo Gomes; Gomes, Maria Vitória Ribeiro; Amback, Beatriz Cruz; Mello Neto, Hudson de; Thomaz, Fernanda Rocha; Mattos, Rodrigo Rinaldi de; Veról, Aline Pires; Sousa, Matheus Martins de; Rezende, Osvaldo Moura; de Magalhães, Paulo Canedo (Frontiers in Water, 2024)
Cities are increasingly dealing with challenges regarding the negative impact of rapid and mismanaged urbanization. Therefore, city planning must cope with the natural environment limitations, seeking a balance between the human activities and the well-functioning of the hydrologic cycle. This work aims to present a conceptual framework able to properly integrate the stormwater dynamics into the open spaces system in a functional way, establishing a Hydrological Interest Area, HIA, to structure urban expansion integrated into and respecting watershed natural processes. The initial step is to define a HIA, primarily consisting of open spaces that can be used for supporting urban drainage functions and to order land use in the urban expansion process. This delimitation offers the background for interpreting the watershed in three functional arches, especially covering the upstream, mid-reach and downstream areas of the basin, guiding the design of a set of flood mitigation interventions focusing on the use of Blue-Green Infrastructure. To illustrate and validate the proposed methodological framework, the design is evaluated by a flood modeling tool, using a hydrological-hydrodynamic cell-model. A case study was driven in the Bambu Watershed, a rapidly developing area in the municipality of Maricá, Rio de Janeiro, Brazil. The proposed intervention includes an urban expansion scenario for a low impact development on flood behavior alongside with four parks: an upstream park with reservoirs, two multifunctional floodable urban parks, and a park dedicated to lagoon restoration. This plan complements riverbed modifications designed to enhance water discharge. The simulation showed significant reduction of water depths with a consequent decrease in exposure of buildings and roads, especially in the most critical region of the watershed. This framework highlights the importance of a multifunctional approach in land use and serves as a robust foundation for controlling urban expansion and proposing projects.